Menggali Teori Kognitivistik Dalam Dunia Pembelajaran - Intan Dwi Safitri; Rizkika Qurroti A'yunina; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
This article aims to examine the cognitive theory of learning, which emphasizes that learning is an active process in which individuals process information, build understanding, and develop thinking skills. This theory states that learning is not just about receiving information, but also how the information is processed and organized in the mind, emphasizing understanding, connecting concepts, and their application in different situations. This study uses a qualitative approach with a descriptive method, identifying sources of information through articles, journals, and relevant literature. The results of the study indicate that cognitive theory emphasizes the importance of learning experiences that stimulate students' thinking, as well as the need to understand the differences in how students think and those of adults. This article also discusses figures who have contributed to cognitive theory.